2017
DOI: 10.2147/cia.s115945
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and delirium, the outcomes in elderly hip fracture patients

Abstract: BackgroundDelirium in hip fractured patients is a frequent complication. Dementia is an important risk factor for delirium and is common in frail elderly. This study aimed to extend the previous knowledge on risk factors for delirium and the consequences. Special attention was given to patients with dementia and delirium.MethodsThis is a retrospective cohort study performed in the Amphia Hospital, Breda, the Netherlands. A full electronic patient file system (Hyperspace Version IU4: Epic, Inc., Verona, WI, USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
166
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 43 publications
21
166
4
5
Order By: Relevance
“…However, clinical observations and previous retrospective studies have suggested a higher impact of cognitive impairment on mortality in these patients.…”
Section: Discussionmentioning
confidence: 77%
“…However, clinical observations and previous retrospective studies have suggested a higher impact of cognitive impairment on mortality in these patients.…”
Section: Discussionmentioning
confidence: 77%
“…Los factores de riesgo más importantes son la demencia previa y la edad avanzada (5)(6) (7) . Es un evento prevenible hasta en un 40%, lo que resalta la importancia de su prevención, diagnóstico y tratamiento (5)(8)(9) (10) .…”
Section: Liativosunclassified
“…1,4,5 Dementia, functional decline, vision impairment, history of alcohol abuse and advanced age are the leading factors associated with delirium that have been recognized on admission in both medical and non-cardiac surgery populations. 7 In the present prospective study, we analyzed the impact of delirium on short-term outcomes in HF patients admitted to an orthogeriatric share care unit where a protocol of approach to delirium was implemented. 3,6 Similarly, dementia is one of the strongest risk factors contributing to delirium, but the effects of dementia on outcomes after delirium have been hardly described in older HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Similarly, dementia is one of the strongest risk factors contributing to delirium, but the effects of dementia on outcomes after delirium have been hardly described in older HF patients. 7 In the present prospective study, we analyzed the impact of delirium on short-term outcomes in HF patients admitted to an orthogeriatric share care unit where a protocol of approach to delirium was implemented. Special attention was given to patients with delirium and dementia.…”
Section: Introductionmentioning
confidence: 99%